Method for encoding characters in coherent optical channel of integrated telecommunication technology - Тіхонов, Віктор Іванович (Eastern-European Journal of Enterprise Technologies, 2013)
An improved method for encoding characters in a coherent optical channel based on the tensor phase modulation, which extends the range of phase modulation to the total phase circle, was developed. For describing the electric signal at the output of coherent photodetector with quadratic characteristics in the homodyne detection mode the tensor model of optical signals interference on the photodiode was proposed. Based on two orthogonally polarized sub-channels of a single optical carrier, a model of complex transmission channel, which provides a virtual extension of dynamic range of phase modulation, was developed. The improved method for encoding characters with the help of orthogonal harmonics, which are generated by phase modulation, was proposed. Each harmonic spectrum encodes one bit of the character in the ternary code that allows transferring special characters in order to control digital flow in the optical channel.